2015
DOI: 10.1093/annhyg/mev060
|View full text |Cite
|
Sign up to set email alerts
|

Mesothelioma among Motor Vehicle Mechanics: An Updated Review and Meta-analysis

Abstract: This meta-analysis of the epidemiologic studies provides evidence that motor vehicle mechanics, including workers who were engaged in brake repair, are not at an increased risk of mesothelioma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 43 publications
3
18
0
Order By: Relevance
“…Several studies have shown that worker exposure to asbestos in occupations where routine exposure to ACM is expected (heavy construction equipment, automobile brakes, and plane parts) is consistent with the OSHA PEL [4] [5] [6] [7] [8]. Those findings are also consistent with the lack of epidemiological evidence for enhanced asbestos-related disease among motor vehicle mechanics and heavy equipment brake removal [9] [10].…”
Section: Introductionsupporting
confidence: 66%
“…Several studies have shown that worker exposure to asbestos in occupations where routine exposure to ACM is expected (heavy construction equipment, automobile brakes, and plane parts) is consistent with the OSHA PEL [4] [5] [6] [7] [8]. Those findings are also consistent with the lack of epidemiological evidence for enhanced asbestos-related disease among motor vehicle mechanics and heavy equipment brake removal [9] [10].…”
Section: Introductionsupporting
confidence: 66%
“…As such, it would be expected that such a documented exposure may lead to an excess risk of MM. However, numerous epidemiological studies have yet to demonstrate an excess risk of 'asbestos'-related disease including MM within this exposure cohort (Wong 2001;Goodman et al 2004;Laden et al 2004;Garabrant et al 2016). It is important to note however that such epidemiological conclusions are not universally shared (Egilman and Billings 2005) and furthermore, there are case studies describing MM in auto mechanics working with chrysotile containing friction products (Langer and McCaughey 1982;Finkelstein 2015).…”
Section: Introductionmentioning
confidence: 90%
“…Response: It is true that many lawsuits were filed but, in the view of a number of experts, including me, it is false to claim that the cause of the mesothelioma in virtually all mechanics who developed the disease was exposure to brake dust (known as brake wear debris). 3,48,49 In my experience and the experience of a number of other experts, having reviewed many such cases, the cause of the mesothelioma, in the vast majority of vehicle mechanic cases, based on the weight of evidence, was nearly always due to significant exposure to amphiboles that had nothing to do with their work as a mechanic. In some cases, there was ample evidence of a misdiagnosis, inadequate latency, tissue specific medical radiation during childhood, or a spontaneous mesothelioma in an elderly adult who lacked significant exposure to amphiboles (like virtually all cancers, the incidence of mesothelioma in the general population is much greater in the elderly).…”
Section: When Unsupported Claims Are Leveled Against Corporations Asmentioning
confidence: 99%
“…In the view of these same scientists, the low potency of chrysotile, the lack of biologic activity of brake wear debris and raw brake dust (like from a grinder), the low dose (concentration x time), and the epidemiology data all strongly indicate that the risk of mechanics developing mesothelioma due to their work as mechanics was de minimis. 3,[48][49][50][51][52][53][54][55][56][57] It is recognized that some scientists and physicians believe the evidence is that brake dust has produced mesothelioma in some mechanics, as evidenced in numerous amicus briefs on this matter. 58 Lynch et al 56 more than 50 years ago, Jacko et al, 57 and others showed that brakewear debris should likely not be an asbestos hazard due to fiber size, clumping and conversion to forsterite.…”
Section: When Unsupported Claims Are Leveled Against Corporations Asmentioning
confidence: 99%
See 1 more Smart Citation